Produktivitas Budidaya Udang Vaname (Litopenaeus vannamei) Berdasarkan Faktor Kualitas Air, Pertumbuhan, Efisiensi Pakan, dan Analisa Usaha - Muhammad Akbarurrasyid; Ega Aditya Prama; Hemallya Fadila; Dinno Sudinno; Wahyu Puji Astiyani; Irvan Firman Syah Zainal Arifin (Universitas Mataram, 2026)
The productivity of whiteleg shrimp (Litopenaeus vannamei) cultivation is influenced by technical and non-technical factors. Technical factors include water quality, growth and survival, and feed efficiency. Non-technical factors, such as business analysis and feasibility, are related to cultivation productivity. The study was conducted in Pandeglang, Banten, Indonesia, for three months. Six ponds were observed, each with an area of 2.500 m2, 2.000 m2 and 1.500 m2, with a stocking density of 125 shrimp/m2 . The results showed that water quality was mostly within the optimal range, except for parameters such as brightness, nitrite, ammonium, ammonia, phosphate, Total Organic Matter (TOM), and magnesium. The growth values of Average Body Weight (ABW) and Average Daily Growth (ADG) were very good, with a low mortality rate or high SR, and optimal feed efficiency throughout the pond. The results of the business analysis show a positive value on the productivity of L. vannamei. In general, productivity factors such as water quality, growth and survival, feed efficiency and business analysis are related to biomass production with R2 values, namely: 0.9942 (pond 1), 0.9922 (pond 2), 0.9956 (pond 3), 0.9598 (pond 4), 0.9903 (pond 5) and 0.9844 (pond 6).